Rethinking Regenerative Medicine: A Macrophage-Centered Approach - Brown, Bryan N.; Sicari, Brian M.; Badylak, Stephen F. (Frontiers in Immunology, 2014)
Regenerative medicine, a multi-disciplinary approach that seeks to restore form and function to damaged or diseased tissues and organs, has evolved significantly during the past decade. By adapting and integrating fundamental knowledge from cell biology, polymer science, and engineering, coupled with an increasing understanding of the mechanisms which underlie the pathogenesis of specific diseases, regenerative medicine has the potential for innovative and transformative therapies for heretofore unmet medical needs. However, the translation of novel technologies from the benchtop to animal models and clinical settings is non-trivial and requires an understanding of the mechanisms by which the host will respond to these novel therapeutic approaches. The role of the innate immune system, especially the role of macrophages, in the host response to regenerative medicine based strategies has recently received considerable attention. Macrophage phenotype and function have been suggested as critical and determinant factors in downstream functional outcomes. The constructive and regulatory, and in fact essential, role of macrophages in positive outcomes represents a significant departure from the classical paradigms of host-biomaterial interactions, which typically consider activation of the host immune system as undesirable. It appears desirable that emerging regenerative medicine approaches should not only accommodate, but promote, the involvement of the immune system to facilitate positive outcomes. Herein, we describe the current understanding of macrophage phenotype as it pertains to regenerative medicine and suggest that improvement of our understanding of context-dependent macrophage polarization will lead to concurrent improvement in outcomes.